Canada : Selected Issues. (IMF Staff Country Reports; Country Report, 2001)
Between 1980 and 1995, labor productivity in the business sector grew at an average annual rate in Canada, which was slightly faster than productivity growth in Germany, but significantly slower than labor productivity growth in France, Italy, Japan, and the United States. To better understand developments in labor productivity, it is useful to decompose its growth rate into changes in the capital/labor ratio and in total factor productivity. The contribution of information technology to labor productivity growth has been more modest in Canada than in the United States.